The study of the daily dynamics of the accommodative function of the eye - I. G. Ovechkin; G. A. Emelyanov (Oftalʹmologiâ, 2014)
Purpose: to study the dynamics of the volume was an accommodation during the day.Methods: We investigated the amount of accommodation in 36 patients (men aged 25-30 years) without pathology of the vision five times during the day.Results: the highest rates were observed in the amount of accommodation from 12 to 16 hours, the maximum oscillation is 1.34 D or 24.3%.Conclusion: the analysis of the accommodative function of the various problems of ophthalmology and alternative specialties (neurology, rehabilitation medicine, etc.) must be compared the identified changes in the state of the accommodative apparatus of an eye to possible biological rhythms during the day.